(untitled) (Ciencias Veterinarias, 2021)
An adult, Ibero breed, equine gelding, with a clinical history of “several ulcers and inflammations all over the body, plus a chronic loss of condition” is attended. The farm veterinarian sent biopsy samples to a private pathology laboratory and referred the horse to the Equine Hospital, School of Veterinary Medicine, at the Universidad Nacional de Costa Rica. While the patient was hospitalized, the results from the private pathologist were received, and a diagnosis of “equine histiocytic non-epitheliotropic cutaneous lymphoma” was made. The horse was humanely euthanized, and the body was examined at the Department of Pathology. Necropsy reports the most relevant macroscopic & microscopic findings and confirms the diagnosis of “T-cell rich B-cell lymphoma (histiolymphocytic cutaneous lymphoma).” The histopathological results from examining several organs of the patient showed the presence of an abundant mononuclear infiltrate composed of lymphocytes, histiocytes, and some plasmatic cells. Considering that dermatological pathologies are amongst the first two groups of diseases affecting horses, it is of paramount importance to include this disease in the differential diagnosis.